Intraventricular hemorrhage as a risk factor for retinopathy of prematurity - S.V. Katsan; A.O. Adakhovska; E.S. Budivska (Journal of Ophthalmology, 2020)
Background: Practically any body system in the premature infant is at risk of injuries, with the leading ones being perinatal central nervous system injury and visual system injury.